Ecological contribution index: A simple and reliable method to estimate range condition: INDICE DE CONTRIBUCIÓN ECOLÓGICA DE PASTIZALES - Saucedo-Terán, Rubén A.; Jurado-Guerra, Pedro; Rubio-Arias, Héctor O.; Álvarez-Holguín, Alán (Ecosistemas y Recursos Agropecuarios, 2021)
Current rangeland assessment techniques show constraints making them difficult to use. Our objective was to propose and describe a reliable and simple method to evaluate rangelands. The method consists of a rangeland ecological contribution index (RECI) through estimation of four indicators. Range condition and RECI were estimated at 29 beef cattle ranches. Range condition was calculated by COTECOCA (Climax) methodology. RECI was estimated through visual observations of total vegetation cover, perennial forage species cover, water retention capacity, and soil stability. Data collected were analyzed by Chi-Square test, correspondence analysis, and logistic regression to determine their reliability. No statistical evidences (p<0.01; Chi-Square) were found that support independence between RECI and range condition data at all vegetation types. Also, correspondence analysis and ordinal logistic regression (Goodman-Kruskal´s gamma = 0.91; p<0.01) showed a close relationship between results of RECI and range condition.